Anatomical changes in brown and beige fat development in response to changes in diet and ambient temperature in virgin and pregnant rats - Albustanji, Layla Ahmad Mohammad (2019)
Brown adipose tissue (BAT) can rapidly generate heat following the activation of its unique mitochondrial uncoupling protein (UCP) 1 which may therefore have a role in regulating energy balance. The main anatomical location of BAT in rodents is the interscapular region, although thermogenic adipocytes termed beige can develop within white adipose tissue (WAT). As cold exposure is the main factor promoting BAT activity and browning in WAT, my thesis investigated the influence of housing at a mild cold temperature of 20°C on the interscapular BAT activity and the browning capacity of omental and inguinal WAT. This study also examined the potential effect of pregnancy on these depots and whether inguinal adipocytes transform to mammary cells (by a process termed pinking) through gestation. Excess adiposity is also associated with low-grade inflammation characterised by adipocyte hypertrophy and hyperplasia and referred to as meta-inflammation. I, therefore, studied the effect of housing temperature on biomarkers of inflammation in omental fat in response to an obesogenic diet and whether this was further affected by pregnancy. The extent to which mild cold exposure would modulate any adaptations were also examined. The overall aim of my thesis was to identify the consequences of housing temperature on UCP1 and gene markers of brown adipocyte development in order to determine how it can modulate dietary-induced obesity. Female Sprague Dawley rats were fed either a standard (18% of energy from fat; 24% from protein; 58% from carbohydrates, of which 7% are mono- and disaccharides; energy density of 3.1 kcal/g), or an obesogenic diet that was high in fat and sucrose (39% of energy from fat; 23% from protein; 39% from carbohydrate, of which 44% are mono- and disaccharides; energy density of 4.6 kcal/g) and housed at either a cool i.e. 20°C, or thermoneutral i.e. 27°C temperature. Body weight was recorded three times a week and food intake was measured, but only prior to pregnancy. Animals were tissue sampled, either before pregnancy or at 10 and 19 days of gestation which corresponds to 50% and 90% of the term; respectively. Expression of genes associated with thermogenesis, browning, pinking, inflammation and fatty acids metabolism were measured using qPCR while histological appearance was determined in H & E stained sections. The obesogenic diet resulted in more fat accumulation. UCP1 protein in iBAT was more abundant in virgin animals fed the high energy diet at mild cold than at thermoneutrality. This response was modulated with pregnancy whereby UCP1 protein expression was similar between all groups. UCP1 gene expression was similar between groups but there was a decline in mRNA abundance for UCP1 with gestation that was more pronounced at 20°C. UCP1 mRNA was not detected in inguinal or omental adipose tissue in any group. Inguinal adipocytes transformed to alveolar epithelial cells with gestation as determined by changes at the gross, histological and molecular levels. Histologically, inguinal adipocytes looked more compact as gestation proceeded and alveoli formation was apparent. Gene expression for mammary cell markers ELF5 and WAP, increased with gestation, which are indicative of alveologenesis and the capacity to synthesise milk. There was no effect of diet or temperature on gene expression for pro-inflammatory markers NFkB and TNFα or anti-inflammatory genes e.g. IL10 biomarkers in response to housing temperature or diet but pro-inflammatory markers declined as pregnancy progressed. In conclusion, housing at a standard temperature enhanced brown characteristics in iBAT. Mild cold exposure could therefore be an effective strategy to reduce fat deposition and thus obesity through enhanced thermogenesis. Exposure of dams to such conditions may subsequently influence the extent to which their offspring develop obesity in later life and reduce the negative effects on the mother.